Chlamydia screening and prophylactic treatment in termination of pregnancy clinics in the Netherlands and Great Britain: a qualitative study. (1st November 2016) - van den Berg, Georgina F.; Picavet, Charles; Hoopman, Rianne; Lohr, Patricia A.; Op de Coul, Eline L. M.
Abstract: Background: Women having a termination of pregnancy (TOP) have higher rates of Chlamydia trachomatis (CT) than the general population. In this study, we explored CT treatment and prevention in Dutch TOP clinics in comparison to that provided in Great Britain (GB). Methods: A qualitative study including 14 semi-structured interviews with health care professionals (HCPs) in TOP clinics (the Netherlands: 9, GB: 5). Interviews were recorded, transcribed, and analysed by thematic content analysis. Results: Prophylactic treatment with azithromycin is routinely prescribed after surgical TOP, but not after medical TOP ('abortion pill'). Sexually transmitted infections (STI) tests are offered to clients who are considered at high risk of having STI. Uptake varies according to health insurance coverage of STI testing. Some Dutch clinics are able to provide free testing for women under 25 years of age. Sexual health counselling is often limited to discussing birth control. The major difference between the Netherlands and GB is that GB TOP clinics more often offer free STI testing and prophylaxis to their clients. Conclusion: HCPs in Dutch TOP clinics consider STI testing an important part of their service, but financial barriers prevent testing on location. Dutch TOP clinics should offer STI tests to all women, and collaboration with public health services could improve STI testing and counselling for young people. Furthermore, clinics should treat all TOP clients with prophylactic azithromycin. This could prevent CT and other upper genital tract post-abortion infections.